Antiepileptic and central nervous system depressant activity of Sechium edule fruit extract - Sayeed Mohammed Firdous Mumtaz (Bangladesh Journal of Pharmacology, 2012)
The effect of ethanol extract of fruits of Sechium edule  on antiepileptic and central nervous system (CNS) depressant model was studied in rats. The extract (200 mg/kg body weight, orally) significantly reduced the duration of various phases of convulsions in both MES-induce seizures and in PTZ-induced convulsion. In CNS depressant model, the locomotor activity was also decreased in a dose dependent manner as compared to control group the extract and the rota rod test revealed a significant loss of muscular coordination.